The deep end : a memoir of growing up - Callaghan, Mary Rose (University of Delaware Press ; Copublished by the Rowman and Littlefield Publishing Group, Incorporated, 2016)
"The Deep End is the coming-of-age memoir of Irish author Mary Rose Callaghan. Here Callaghan closely examines her relationship with her mother-which endured through economic hardship, and her mother's descent into mental illness and alcoholism-in addition to Mary Rose's own difficult childhood and later triumphs as a writer."--